2004
DOI: 10.1093/carcin/bgh131
|View full text |Cite
|
Sign up to set email alerts
|

DNA adducts in tumour, normal peripheral lung and bronchus, and peripheral blood lymphocytes from smoking and non-smoking lung cancer patients: correlations between tissues and detection by 32P-postlabelling and immunoassay

Abstract: Smoking is a major risk factor for lung cancer. This comparative study of smoking-related carcinogen-DNA adducts in pulmonary tissues and peripheral blood lymphocytes aims to further explore the primary DNA damaging processes by cigarette smoke in target and surrogate tissues. Samples of tumour and normal peripheral lung tissue, normal bronchial tissue and peripheral blood lymphocytes were obtained from a total of 85 lung cancer patients who underwent lung resection. Bulky DNA adducts were determined by 32P-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
2

Year Published

2008
2008
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 34 publications
0
31
2
Order By: Relevance
“…54 Recently, it was shown that the DNA content of N7-methylguanine produced from N-nitroso compounds was higher in urinary bladder Schistosomal tumor tissues than in adjacent normal epithelium of Egyptian patients. 55 In contrast, previous findings 56 showed lower DNA adducts levels in tumor DNA when compared with DNA from adjacent normal tissue. The very clear differences indicate that the close correlation between the levels of DNA alkylation in normal and tumor tissue despite the very large difference in the levels of DNA damage might be partially correlated to the individual differences in modes of alkylating agent metabolism due to genetic polymorphism and/or DNA repair pathways.…”
Section: Discussionmentioning
confidence: 73%
“…54 Recently, it was shown that the DNA content of N7-methylguanine produced from N-nitroso compounds was higher in urinary bladder Schistosomal tumor tissues than in adjacent normal epithelium of Egyptian patients. 55 In contrast, previous findings 56 showed lower DNA adducts levels in tumor DNA when compared with DNA from adjacent normal tissue. The very clear differences indicate that the close correlation between the levels of DNA alkylation in normal and tumor tissue despite the very large difference in the levels of DNA damage might be partially correlated to the individual differences in modes of alkylating agent metabolism due to genetic polymorphism and/or DNA repair pathways.…”
Section: Discussionmentioning
confidence: 73%
“…Consistent with what we have previously reported (7,8), adduct levels were higher in nontumor cells compared with tumor cells. Several studies of other tissues that measured PAH-DNA adducts in both tumor and adjacent nontumor cells, including lung (38), laryngeal (39), pancreas (40), and liver (41), have also reported higher Research.…”
Section: Discussionmentioning
confidence: 98%
“…Molecular epidemiology studies have shown that PAH-(B[a]P)-DNA adduct formation in the peripheral blood lymphocytes (PBL) is an index of exposure also of the target tissues (i.e., lung; refs. 4,5). Anti -B[a]PDE-DNA adduct detection in the accessible tissues (PBLs) has allowed us to show genotoxic exposure to PAHs in occupational (cokeries) and environmental (smoking, diet, and environmental) situations (6,7).…”
Section: Introductionmentioning
confidence: 99%